Mathematical Design of Shell-and-Tube Heat Exchanger for MEK Production - Damanik, Vizny Grace Irene; Nandiyanto, Asep Bayu Dani; Kurniawan, Teguh (Jurnal Pemberdayaan Umat, 2025)
Purpose: This study aims to analyse and develop design a heat exchanger (HE) for the production of Methyl Ethyl Ketone (MEK) which will be compiled into a computational program for the design of shell-tube type HE. Methodology: The problem with this HE is that the temperature of 2-butanol is 30?C from the storage tank. While the HE reactor requires a temperature of 99.6?C, HE plays a role in increasing the temperature from 30?C to 99.6?C. To be more energy efficient, researchers used heat of the product, MEK. Which is where to exchange heat from the product to the reactants. The design of a shell-tube two-pass exchanger with a working fluid in the form of 2-butanol as a hot fluid with water as a cold fluid. Results: Thus, HE with shell and tube doesn’t meet the requirements and standards of TEMA. Although the shell and tube type of HE doesn’t conform to the criteria and standards specified in industrial applications, the analysis can be used as a learning tool for the design process, heme performance analysis, and operating mechanism of the HE. Limitations: This research is focused on developing HE designs for the production of MEK. Contribution: This research can provide a reference for designing HE in industrial development. Conclusion: The designed shell-and-tube heat exchanger shows limited efficiency and does not comply with TEMA industrial standards. However, the study provides valuable insights into the design methodology and serves as a foundation for further optimization of heat exchanger systems to enhance performance, efficiency, and industrial applicability.